Imaging and imagining Palestine : photography, modernity and the biblical lens, 1918-1948 - Sanchez-Summerer, Karene; Zananiri, Sary (Middle East and Islamic Studies E-Books Online, Collection 2021, ISBN: 9789004441286., 2021)
"Imaging and Imagining Palestine is the first comprehensive study of photography during the British Mandate period (1918-1948). It addresses well-known archives, photos from private collections never available before and archives that have until recently remained closed. This interdisciplinary volume argues that photography is central to a different understanding of the social and political complexities of Palestine in this period. While Biblical and Orientalist images abound, the chapters in this book go further by questioning the impact of photography on the social histories of British Mandate Palestine. This book considers the specific archives, the work of individual photographers, methods for reading historical photography from the present and how we might begin the process of decolonising photography"--